Reproductive biology of the Magellan skate, Bathyraja magellanica (Chondrichthyes, Rajidae), in the south-western Atlantic - Scenna, Lorena Beatriz (2014)
The knowledge of reproductive parameters is essential to develop effective management and conservation plans. The present study provides the first information on the reproductive biology of an abundant and important trawl by-catch skate, Bathyraja magellanica, along its geographic range in the south-western Atlantic (43-55°S). In total, 81 males (205-738mm total length, TL) and 104 females (157-768mm TL) were analysed. Length-frequency distributions were significantly different between sexes, with females being larger than males. However, no sexual dimorphism was observed in TL-total body weight relationship and liver size. Length at maturity was similar between males (638mm TL) and females (653mm TL), ∼85% of maximum observed size. The mean number of vitellogenic oocytes per skate was 14.37 (±4.43), increasing with female TL. Egg cases of B. magellanica had striated surface, broad lateral keels, extremely long posterior horns, and its wall consisted of three layers. An important area for the reproduction of B. magellanica was found between 48°50′S and 50°30′S. The present results indicated that this species has a low reproductive efficiency, suggesting that the B. magellanica population should be monitored closely to avoid large-scale changes in skate community structure of the south-western Atlantic.